Tranzitorna tahipnea novorođenčadi - potreba za dodatnim kiseonikom i moguće komplikacije - Jakovljević, Tamara (Medical Research, 2022)
Transient tachynpea of the newborn, a self-limiting condition, in some cases requires invasive respiratory support. This study aimed to investigate the influence of gestational age and mode of delivery on oxygen therapy, and appearance of complications. This retrospective study covered data about children born during one year and diagnosed with transient tachypnea. Duration of oxygen therapy and assessment of complications were analyzed according to the mode of delivery and gestational age. In 77,3% cases transient tachypnea was well-managed with the use of oxygen therapy in incubator. In relation to the mode of delivery and gestational age, no significant difference in duration of different oxygen therapy types were observed. Two newborns developed persistent pulmonary hypertension, and one pneumothorax. Invasive respiratory support is not frequently used in transient tachypnea. Persistent pulmonary hypertension and air leak syndrome are possible, but very rare complications of this condition.